Efektivitas Gerakan Senam Dasar dalam Meningkatkan Konsentrasi Belajar Anak - Mulyana, Agus; Adriawan, Aura Nazwa Ar’zahra; Safitri, Awalia; Dwitami, Dena; Melisa, Dhea Citra; Hanapiah, Frisian Nur; Khotimah, Humairo Husnul; Mansyur, Larissa Suci Amalia Salwa (Indo-MathEdu Intellectuals Journal, 2024)
Learning concentration is the ability to concentrate on the learning process, very important for students because it supports good understanding and memory. This study aims to determine the effectiveness of basic gymnastics in improving children's learning concentration. This study uses a qualitative approach through literature review to collect, evaluate, and synthesize data from various sources about the research subject. Articles published on Google Scholar are the source of data for these research articles. The data analysis used is qualitative data analysis consisting of data reduction, data submission, and conclusion drawing. The findings of this study are that this physical activity can stimulate blood flow to the brain, improve cognitive function, and reduce stress and anxiety. Through basic gymnastics movements, children can learn to be more focused, disciplined, and organized in completing school assignments. Basic gymnastics also helps children develop social and emotional skills, such as cooperation and self-control, which are very useful in a learning environment. Routinely doing basic gymnastics provides an energy boost that can help children cope with boredom, allowing them to stay awake and focused during study sessions. Thus, basic gymnastics is an effective and enjoyable method to improve the learning concentration of elementary school students, providing long-term benefits for cognitive and physical development